General Education Oversight Committee 10-26-21 Proposed Amendment, 2021-2022 - Salisbury University Faculty Senate (My University, 2021)
Proposed amendment for the establishment of advisory subcommittees for the proposed General Education Oversight Committee.
Keywords: Governance Consortium; Shared Governance